POLA PERILAKU MENCARI BANTUAN PADA KELUARGA PASIEN GANGGUAN JIWA - Subandi, -; Utami, Muhana Sofiati (Faculty of Psychology, Universitas Gadjah Mada, 1996)
The focus of this research is to identify care seeking behaviorof the family whose one of its members suffer from mental illness. The data was gathered from interview with 20 respondents who took the patient to see the doctor in Lali Jiwo mental Hospital, Pakem Yogyakarta.